No pain, no gain? In defence of genetically disenhancing (most) research animals - Devolder, K; Eggel, M (MDPI, 2019)
Every year, around 12 million animals are used for the purpose of scientific research in the European Union alone. The procedures performed on them often cause significant pain and suffering. Despite regulations aimed at reducing this suffering, we can expect millions of research animals to continue to suffer in the near to mid-term future. Given this reality, we propose the use of gene editing to create research animals with a reduced capacity for suffering, in particular, from pain. We argue that our proposal would be in line with moral principles embedded in European regulations regarding animal research, and that it would facilitate compliance with these regulations. We also respond to the strongest argument against our proposal-the 'no pain no gain' argument.